Drinking water tank coating and preparation method and application thereof
A water-based coating for drinking water tanks, utilizing modified nano-silica and chitosan-silane coupling agents, addresses adhesion and corrosion issues, offering superior durability and environmental safety.
Patent Information
- Application Number
- CN202411568904.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-11-05
AI Technical Summary
Existing solvent-free epoxy coatings for drinking water tanks and pipelines face challenges in adhesion and anti-corrosion performance, particularly in complex and confined spaces, necessitating improved coatings with enhanced durability and environmental safety.
A water-based coating comprising components A and B, where component A includes epoxy resin, dispersants, defoamers, titanium dioxide, talcum powder, and water, and component B is a modified curing agent prepared through a process involving nano-silica modification with chitosan and silane coupling agents, ensuring excellent adhesion and corrosion resistance.
The coating exhibits superior anti-corrosion performance, low VOC emissions, and non-toxicity, providing reliable protection for drinking water tanks and pipelines with extended service life and environmental safety.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coatings, and in particular to a drinking water tank coating, a preparation method thereof and an application thereof. Background Art
[0002] At present, the anti-corrosion coatings used for the inner wall of drinking water tanks and drinking water distribution pipelines and equipment are mostly solvent-based epoxy coatings and solvent-free epoxy coatings. Among them, solvent-free epoxy coatings do not contain volatile solvents (VOCs), have the characteristics of less volatile substances after film formation, low VOC emissions, and no water pollution. It provides a reliable guarantee for the hygienic safety of air quality and water quality in drinking water tanks and drinking water distribution pipelines and equipment, and is an important development trend of drinking water tank coatings.
[0003] However, drinking water tanks and drinking water distribution pipelines and equipment generally have narrow space, complex structure, dark and damp characteristics, which cause inconvenience to the construction and maintenance of inner wall protective coatings. Therefore, it is necessary to take protective measures to improve the adhesion and anti-corrosion properties of solvent-free drinking water tank coatings and extend the service life of the coating while ensuring that it is non-toxic and solvent-free.
[0004] In Chinese patent CN105017938A, a composition of E44 bisphenol A epoxy resin, bisphenol F epoxy resin, AGE epoxy active diluent, modified polyamide and modified alicyclic amine is used as the main film-forming substance, and a high-carbon straight-chain aromatic polymer is used as a plasticizer modified formula to obtain a solvent-free drinking water pipe coating with an adhesion of 10MPa and a salt spray resistance of 1500h.
[0005] In Chinese patent CN102352171A, the adhesion and anti-corrosion properties of the coating are improved by modifying fillers such as hollow microspheres and cellulose and using adhesion promoters, resulting in a new type of environmentally friendly coating with an adhesion of 15MPa and a salt spray resistance of 1440h, which can be used for drinking water tanks and is super resistant to marine environment corrosion.
[0006] Although the anti-corrosion performance of the drinking water tank coating has been improved to a certain extent by optimizing the formula through the above method, it is still difficult to meet the requirements of long-term anti-corrosion. Summary of the invention
[0007] The purpose of the present invention is to propose a drinking water tank paint and its preparation method and application. The paint is a water-based paint with less chronic volatile substances after film formation, low VOC emissions, excellent anti-corrosion performance, non-toxicity, and no water pollution. It provides reliable protection for the air quality, anti-corrosion and sanitary safety of water quality in the drinking water tank and can be widely used.
[0008] The technical solution of the present invention is achieved in this way:
[0009] The present invention provides a drinking water tank coating, comprising component A and component B, with a mass ratio of 100:10-15, wherein the component A is prepared from the following raw materials in parts by weight: 20-30 parts of epoxy resin, 0.3-0.5 parts of aqueous dispersant, 0.3-0.5 parts of aqueous defoamer, 5-10 parts of titanium dioxide, 10-15 parts of talcum powder, 0.3-0.5 parts of aqueous wetting agent and 20-40 parts of water; the component B is a modified curing agent;
[0010] The preparation method of the modified curing agent is as follows:
[0011] S1. Add water and ammonia to ethyl orthosilicate solution in ethanol, heat and stir to react, centrifuge, wash, dry, and calcine to obtain nano-silicon dioxide;
[0012] S2. The nano-silica was added to a Tris-HCl solution, dopamine hydrochloride was added, the reaction was heated and stirred, centrifuged, washed, and dried to obtain modified nano-silica;
[0013] S3. The chitosan was dissolved in an acid solution, modified nano-silica was added, the reaction was stirred, centrifuged, washed, and dried to obtain chitosan-coated nano-silica;
[0014] S4. Add chitosan-coated nano-silica into ethanol, add a composite silane coupling agent, heat and stir to react, centrifuge, wash, and dry to obtain a modified curing agent.
[0015] As a further improvement of the present invention, the aqueous dispersant is 5040, the aqueous defoamer is BYK-017, the aqueous wetting agent is BYK180, and the epoxy resin is epoxy resin 6520.
[0016] As a further improvement of the present invention, the mass ratio of tetraethyl orthosilicate, ethanol, water and ammonia water in step S1 is 15-17:100-120:10-12:5-7, the temperature of the heating and stirring reaction is 35-45°C, the time is 7-10h, and the calcination temperature is 500-600°C, and the time is 1-2h.
[0017] As a further improvement of the present invention, the pH value of the Tris-HCl solution in step S2 is 8.5-9.5, the mass ratio of the nano-silicon dioxide to dopamine hydrochloride is 10:3-4, the temperature of the heating and stirring reaction is 40-50° C., and the time is 4-5 hours.
[0018] As a further improvement of the present invention, the acid solution in step S3 is 1-3wt% acetic acid or lactic acid solution, the mass ratio of chitosan to modified nano-silica is 5-7:10, and the stirring reaction time is 20-40min.
[0019] As a further improvement of the present invention, in step S4, the mass ratio of the chitosan-coated nano-silica to the composite silane coupling agent is 10:2-3, the temperature of the heating and stirring reaction is 35-45°C, the time is 1-3h, and the composite silane coupling agent includes KH550 and KH560, and the mass ratio is 2-4:5.
[0020] The present invention further protects a method for preparing the above-mentioned drinking water tank coating, comprising the following steps:
[0021] (1) Evenly mix epoxy resin, aqueous dispersant, aqueous defoamer, talcum powder, titanium dioxide, aqueous wetting agent and water, disperse at high speed, and grind to obtain component A;
[0022] (2) Mixing the modified curing agent uniformly to obtain component B;
[0023] When in use, component A and component B are evenly mixed in a mass ratio of 100:10-15, applied on the surface of the substrate, and cured at room temperature to obtain a coating.
[0024] As a further improvement of the present invention, the rotation speed of the high-speed dispersion is 1000-1200 r / min, the time is 20-30 min, and the grinding is performed to a fineness of <100 μm.
[0025] The present invention further protects the use of the above-mentioned drinking water tank coating in drinking water tanks and drinking water transmission and distribution pipelines and equipment inner walls.
[0026] The present invention has the following beneficial effects:
[0027] Compounds containing -OH groups can promote the reaction of epoxy resin with nucleophilic substances such as amines, and COC groups are more susceptible to the influence of nucleophilic reagents. During the curing reaction, due to the continuous generation of -OH, the curing reaction of epoxy resin and amine has self-catalytic properties in the initial stage of the reaction, thereby accelerating the curing reaction. Since the surface of the modified curing agent prepared by the present invention is coated with chitosan and contains abundant amino and hydroxyl groups, the different types of oxygen-containing functional groups on its surface have similar catalytic effects to -OH formed during the curing process of epoxy resin, thereby facilitating the curing reaction of epoxy resin and amine curing agents. At the same time, since the surface of the modified curing agent prepared is modified by a silane coupling agent with amino and epoxy groups, the modified curing agent prepared can react with the substrate, thereby making the curing agent have better dispersibility in the epoxy resin matrix, thereby being more conducive to the generation of this catalytic effect.
[0028] The surface of the prepared nano-silicon dioxide is modified by polydopamine, which, on the one hand, helps to form hydrogen bonds with chitosan so that chitosan is coated on the surface of the nano-silicon dioxide, and on the other hand, the polyamino and hydroxyl structures of polydopamine also help to self-catalytically cure the epoxy resin. At the same time, the nano-silicon dioxide core material has a significant modification effect on the mechanical properties, waterproof properties, weather resistance and corrosion resistance of the coating.
[0029] The modified curing agent prepared by the present invention uses the natural product chitosan as a raw material, and does not involve toxic organic solvents in the preparation process. The preparation method is green and environmentally friendly, and no VOC is released. Therefore, when added to the coating for curing, almost no VOC is released. The modified curing agent is green and environmentally friendly, and is more suitable for use in drinking water tanks and drinking water transmission and distribution pipelines and equipment inner walls. Compared with traditional amine curing agents, it is more environmentally friendly and safer.
[0030] The drinking water tank paint prepared by the present invention is a water-based paint, which has less chronic volatile substances after film formation, low VOC emissions, excellent anti-corrosion performance, is non-toxic and does not pollute water quality. It provides reliable guarantees for the air quality, anti-corrosion and sanitary safety of water quality in the drinking water tank and can be widely used. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Preparation Example 1 Preparation of modified curing agent
[0033] The following steps are involved:
[0034] S1. Add 10g of water and 5g of ammonia water to 15g of ethyl orthosilicate solution in 100g of ethanol, heat to 35°C, stir and react for 7h, centrifuge, wash, dry, and calcine at 500°C for 1h to obtain nano-silicon dioxide;
[0035] S2. 10 g of nano-silica was added to 200 mL of Tris-HCl solution with a pH value of 8.5, 3 g of dopamine hydrochloride was added, the mixture was heated to 40° C., stirred for reaction for 4 h, centrifuged, washed, and dried to obtain modified nano-silica;
[0036] S3. 5 g of chitosan was dissolved in 500 mL of 1 wt% acetic acid solution, 10 g of modified nano-silica was added, the reaction was stirred for 20 min, centrifuged, washed, and dried to obtain chitosan-coated nano-silica;
[0037] S4. 10 g of chitosan-coated nano-silica was added to 200 mL of ethanol, 2 g of a composite silane coupling agent was added, the mixture was heated to 35° C., stirred for reaction for 1 h, centrifuged, washed, and dried to obtain a modified curing agent;
[0038] The composite silane coupling agent includes KH550 and KH560, with a mass ratio of 2:5.
[0039] Preparation Example 2 Preparation of modified curing agent
[0040] The following steps are involved:
[0041] S1. Add 12g of water and 7g of ammonia water to 17g of ethyl orthosilicate solution in 120g of ethanol, heat to 45°C, stir and react for 10h, centrifuge, wash, dry, and calcine at 600°C for 2h to obtain nano-silicon dioxide;
[0042] S2. 10 g of nano-silica was added to 200 mL of Tris-HCl solution with a pH value of 9.5, 4 g of dopamine hydrochloride was added, the mixture was heated to 50° C., stirred for reaction for 5 h, centrifuged, washed, and dried to obtain modified nano-silica;
[0043] S3. 7 g of chitosan was dissolved in 500 mL of 3 wt % lactic acid solution, 10 g of modified nano-silica was added, the reaction was stirred for 40 min, centrifuged, washed, and dried to obtain chitosan-coated nano-silica;
[0044] S4. 10 g of chitosan-coated nano-silica was added to 200 mL of ethanol, 3 g of a composite silane coupling agent was added, the mixture was heated to 45° C., stirred for reaction for 3 h, centrifuged, washed, and dried to obtain a modified curing agent;
[0045] The composite silane coupling agent includes KH550 and KH560, with a mass ratio of 4:5.
[0046] Preparation Example 3 Preparation of modified curing agent
[0047] The following steps are involved:
[0048] S1. Add 11 g of water and 6 g of ammonia water to 16 g of ethyl orthosilicate solution in 110 g of ethanol, heat to 40 ° C, stir and react for 8 h, centrifuge, wash, dry, and calcine at 550 ° C for 1.5 h to obtain nano-silicon dioxide;
[0049] S2. 10 g of nano-silica was added to 200 mL of Tris-HCl solution with a pH value of 9, 3.5 g of dopamine hydrochloride was added, the mixture was heated to 45° C., stirred for reaction for 4.5 h, centrifuged, washed, and dried to obtain modified nano-silica;
[0050] S3. 6 g of chitosan was dissolved in 500 mL of 2 wt% acetic acid solution, 10 g of modified nano-silica was added, the reaction was stirred for 30 min, centrifuged, washed, and dried to obtain chitosan-coated nano-silica;
[0051] S4. 10 g of chitosan-coated nano-silica was added to 200 mL of ethanol, 2.5 g of a composite silane coupling agent was added, the mixture was heated to 40° C., stirred for reaction for 2 h, centrifuged, washed, and dried to obtain a modified curing agent;
[0052] The composite silane coupling agent includes KH550 and KH560, with a mass ratio of 3:5.
[0053] Comparative Preparation Example 1
[0054] Compared with Preparation Example 3, the difference is that step S2 is not performed.
[0055] The details are as follows:
[0056] S1. Add 11 g of water and 6 g of ammonia water to 16 g of ethyl orthosilicate solution in 110 g of ethanol, heat to 40 ° C, stir and react for 8 h, centrifuge, wash, dry, and calcine at 550 ° C for 1.5 h to obtain nano-silicon dioxide;
[0057] S2. 6 g of chitosan was dissolved in 500 mL of 2 wt% acetic acid solution, 10 g of nano-silica was added, the reaction was stirred for 30 min, centrifuged, washed, and dried to obtain chitosan-coated nano-silica;
[0058] S3. 10 g of chitosan-coated nano-silica was added to 200 mL of ethanol, 2.5 g of a composite silane coupling agent was added, the mixture was heated to 40° C., stirred for reaction for 2 h, centrifuged, washed, and dried to obtain a modified curing agent;
[0059] The composite silane coupling agent includes KH550 and KH560, with a mass ratio of 3:5.
[0060] Comparative Preparation Example 2
[0061] Compared with Preparation Example 3, the difference is that step S3 is not performed.
[0062] The details are as follows:
[0063] S1. Add 11 g of water and 6 g of ammonia water to 16 g of ethyl orthosilicate solution in 110 g of ethanol, heat to 40 ° C, stir and react for 8 h, centrifuge, wash, dry, and calcine at 550 ° C for 1.5 h to obtain nano-silicon dioxide;
[0064] S2. 10 g of nano-silica was added to 200 mL of Tris-HCl solution with a pH value of 9, 3.5 g of dopamine hydrochloride was added, the mixture was heated to 45° C., stirred for reaction for 4.5 h, centrifuged, washed, and dried to obtain modified nano-silica;
[0065] S3. Add 10 g of modified nano-silica to 200 mL of ethanol, add 2.5 g of a composite silane coupling agent, heat to 40° C., stir to react for 2 h, centrifuge, wash, and dry to obtain a modified curing agent;
[0066] The composite silane coupling agent includes KH550 and KH560, with a mass ratio of 3:5.
[0067] Comparative Preparation Example 3
[0068] Compared with Preparation Example 3, the difference is that step S4 is not performed.
[0069] The details are as follows:
[0070] S1. Add 11 g of water and 6 g of ammonia water to 16 g of ethyl orthosilicate solution in 110 g of ethanol, heat to 40 ° C, stir and react for 8 h, centrifuge, wash, dry, and calcine at 550 ° C for 1.5 h to obtain nano-silicon dioxide;
[0071] S2. 10 g of nano-silica was added to 200 mL of Tris-HCl solution with a pH value of 9, 3.5 g of dopamine hydrochloride was added, the mixture was heated to 45° C., stirred for reaction for 4.5 h, centrifuged, washed, and dried to obtain modified nano-silica;
[0072] S3. 6 g of chitosan was dissolved in 500 mL of 2 wt% acetic acid solution, 10 g of modified nano-silica was added, and the mixture was stirred for 30 min, centrifuged, washed, and dried to obtain chitosan-coated nano-silica, which was the modified curing agent.
[0073] Example 1
[0074] The present embodiment provides a drinking water tank coating, comprising component A and component B in a mass ratio of 100:10-15, wherein component A is prepared from the following raw materials in parts by weight: 20-30 parts of epoxy resin 6520, 0.3-0.5 parts of aqueous dispersant 5040, 0.3-0.5 parts of aqueous defoamer BYK-017, 5 parts of titanium dioxide, 8-12 parts of talc, 0.3-0.5 parts of aqueous wetting agent BYK180 and 20-40 parts of water; and component B is the modified curing agent prepared in Preparation Example 1.
[0075] The preparation method comprises the following steps:
[0076] (1) Evenly mix epoxy resin, aqueous dispersant, aqueous defoamer, titanium dioxide, talcum powder, aqueous wetting agent and water, stir and disperse at 1000-1200 r / min for 20-30 min, and grind to a fineness of <100 μm to obtain component A;
[0077] (2) The modified curing agent prepared in Preparation Example 1 is used as component B;
[0078] When in use, component A and component B are evenly mixed in a mass ratio of 100:10-15, applied on the surface of the substrate, and cured at room temperature to obtain a coating.
[0079] Example 2
[0080] The present embodiment provides a drinking water tank coating, comprising component A and component B in a mass ratio of 100:10-15, wherein component A is prepared from the following raw materials in parts by weight: 20-30 parts of epoxy resin 6520, 0.3-0.5 parts of aqueous dispersant 5040, 0.3-0.5 parts of aqueous defoamer BYK-017, 10 parts of titanium dioxide, 8-12 parts of talcum powder, 0.3-0.5 parts of aqueous wetting agent BYK180 and 20-40 parts of water; and component B is the modified curing agent obtained in Preparation Example 2.
[0081] The preparation method comprises the following steps:
[0082] (1) Evenly mix epoxy resin, aqueous dispersant, aqueous defoamer, titanium dioxide, talcum powder, aqueous wetting agent and water, stir and disperse at 1000-1200 r / min for 20-30 min, and grind to a fineness of <100 μm to obtain component A;
[0083] (2) The modified curing agent prepared in Preparation Example 2 is used as component B;
[0084] When in use, component A and component B are evenly mixed in a mass ratio of 100:10-15, applied on the surface of the substrate, and cured at room temperature to obtain a coating.
[0085] Example 3
[0086] The present embodiment provides a drinking water tank coating, comprising component A and component B in a mass ratio of 100:12, wherein component A is prepared from the following raw materials in parts by weight: 25 parts of epoxy resin 6520, 0.4 parts of aqueous dispersant 5040, 0.4 parts of aqueous defoamer BYK-017, 7 parts of titanium dioxide, 12 parts of talcum powder, 0.4 parts of aqueous wetting agent BYK180 and 30 parts of water; and component B is the modified curing agent prepared in Preparation Example 3.
[0087] The preparation method comprises the following steps:
[0088] (1) Evenly mix epoxy resin, aqueous dispersant, aqueous defoamer, titanium dioxide, talcum powder, aqueous wetting agent and water, stir and disperse at 1100 r / min for 25 min, and grind to a fineness of <100 μm to obtain component A;
[0089] (2) The modified curing agent prepared in Preparation Example 3 is used as component B;
[0090] When in use, component A and component B are evenly mixed in a mass ratio of 100:12, applied to the surface of the substrate, and cured at room temperature to obtain a coating.
[0091] Comparative Example 1
[0092] Compared with Example 3, the difference is that the modified curing agent is prepared by Comparative Preparation Example 1.
[0093] Comparative Example 2
[0094] Compared with Example 3, the difference is that the modified curing agent is prepared by Comparative Preparation Example 2.
[0095] Comparative Example 3
[0096] Compared with Example 3, the difference is that the modified curing agent is prepared by Comparative Preparation Example 3.
[0097] Comparative Example 4
[0098] Compared with Example 3, the difference is that the modified curing agent is a polyamide curing agent (Jinan Jibin Chemical Co., Ltd.).
[0099] Test Example 1
[0100] The carbon steel substrate was pre-treated with the drinking water tank coatings prepared in Examples 1-3 and Comparative Examples 1-4 of the present invention to reach GB 8923 Sa 2.5 level, and the coatings were applied. After curing, the substrate was tested according to Appendix A of GB 5369-2008 "General Technical Requirements for Marine Drinking Water Tank Coatings".
[0101] The results are shown in Tables 1 and 2.
[0102] Table 1
[0103] Group Abrasion resistance (750g / 500r) (g) Adhesion (pull-off method) (MPa) Flexibility (mm) Impact strength (kg·cm) Stain resistance (grade) Detection Methods GB / T 1768-2006 GB / T5210-2006 GB / T 1748-1979 GB / T 1732-2020 GB / T 9780-2013 Example 1 0.003 7.6 0.09 64 0 Example 2 0.002 7.5 0.10 65 0 Example 3 0.002 7.8 0.07 67 0 Comparative Example 1 0.015 6.5 0.13 59 0 Comparative Example 2 0.009 6.9 0.19 53 0 Comparative Example 3 0.029 6.2 0.25 50 1 Comparative Example 4 0.045 5.8 0.30 48 1
[0104] Table 2
[0105] Group Salt spray resistance (2000h) Water resistance (immersed in 60℃ distilled water, 30d) Weather resistance (12 months) Oil resistance (diesel, 48h) Detection Methods GB / T1771-2007 HG / T1733-1993 GB / T9276-1996 HG / T9274-1988 Example 1 The coating does not bubble, fall off or rust. The coating does not bubble, fall off or rust. Discoloration level 0, Powdering level 0, Crack level 0 The coating does not bubble, fall off or soften Example 2 The coating does not bubble, fall off or rust. The coating does not bubble, fall off or rust. Discoloration level 0, Powdering level 0, Crack level 0 The coating does not bubble, fall off or soften Example 3 The coating does not bubble, fall off or rust. The coating does not bubble, fall off or rust. Discoloration level 0, Powdering level 0, Crack level 0 The coating does not bubble, fall off or soften Comparative Example 1 The coating does not bubble, fall off or soften The coating does not bubble, fall off or soften Discoloration level 1, Powdering level 1, Crack level 0 The coating does not bubble, fall off or soften Comparative Example 2 The coating is bubbling, peeling, and rusting The coating is bubbling, peeling, and rusting Discoloration level 1, Powdering level 1, Crack level 1 The coating does not bubble, fall off or soften Comparative Example 3 The coating is bubbling, peeling, and rusting The coating is bubbling, peeling, and rusting Discoloration level 1, Powdering level 1, Crack level 1 The coating does not bubble, fall off or soften Comparative Example 4 The coating is bubbling, peeling, and rusting The coating is bubbling, peeling, and rusting Discoloration level 2, Powdering level 1, Crack level 1 The coating film is bubbling, peeling, and softening
[0106] It can be seen from the above table that the drinking water tank coatings prepared in Examples 1-3 of the present invention have good comprehensive properties.
[0107] Test Example 2 Acute oral toxicity test in mice
[0108] Refer to the acute fixed-dose oral toxicity test method for rodents recommended by the Organization for Economic Cooperation and Development (OECD) (OECD TG 420). Kunming mice weighing 18-22g were selected, half male and half female, and randomly divided into Example 1-3 and Comparative Example 1-4 groups, with 20 mice in each group. The experimental dose was 20,000 mg / kg and was orally administered to the mice once. The experimental subjects were the drinking water tank paint prepared in Example 1-3 or Comparative Example 1-4. The poisoning symptoms and deaths of the mice were observed within 14 days, and the median lethal dose (LD 50 ).
[0109] Results: Except for the death of 4 mice in the control group 4, no animals in the other groups showed obvious abnormal activity and poisoning within 14 days after intragastric administration of the test substance at the experimental dose, and no experimental animals died during the observation period, indicating that the LD 50 The value is greater than 20000mg / kg body weight. According to the disinfectant toxicity classification standard, the drinking water tank paint is actually non-toxic.
[0110] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A drinking water tank coating, characterized in that: The invention comprises component A and component B, with a mass ratio of 100:10-15, wherein component A is prepared from the following raw materials in parts by weight: 20-30 parts of epoxy resin, 0.3-0.5 parts of aqueous dispersant, 0.3-0.5 parts of aqueous defoamer, 5-10 parts of titanium dioxide, 8-12 parts of talc, 0.3-0.5 parts of aqueous wetting agent and 20-40 parts of water; component B is a modified curing agent; The preparation method of the modified curing agent is as follows: S1. Dissolving ethyl orthosilicate in ethanol, adding water and ammonia, heating and stirring the reaction, centrifuging, washing, drying, and calcining to obtain nano-silicon dioxide; S2. The nano-silica was added to a Tris-HCl solution, dopamine hydrochloride was added, the reaction was heated and stirred, centrifuged, washed, and dried to obtain modified nano-silica; S3. The chitosan was dissolved in an acid solution, modified nano-silica was added, the reaction was stirred, centrifuged, washed, and dried to obtain chitosan-coated nano-silica; S4. Add chitosan-coated nano-silica into ethanol, add a composite silane coupling agent, heat and stir to react, centrifuge, wash, and dry to obtain a modified curing agent.
2. The drinking water tank coating according to claim 1, characterized in that: The aqueous dispersant is 5040, the aqueous defoamer is BYK-017, the aqueous wetting agent is BYK180, and the epoxy resin is epoxy resin 6520.
3. The drinking water tank coating according to claim 1, characterized in that: In step S1, the mass ratio of tetraethyl orthosilicate, ethanol, water and ammonia water is 15-17:100-120:10-12:5-7, the temperature of the heating and stirring reaction is 35-45°C, the time is 7-10h, and the calcination temperature is 500-600°C, and the time is 1-2h.
4. The drinking water tank coating according to claim 1, characterized in that: The pH value of the Tris-HCl solution in step S2 is 8.5-9.5, the mass ratio of the nano-silicon dioxide to dopamine hydrochloride is 10:3-4, the temperature of the heating and stirring reaction is 40-50° C., and the time is 4-5 hours.
5. The drinking water tank coating according to claim 1, characterized in that: In step S3, the acid solution is 1-3wt% acetic acid or lactic acid solution, the mass ratio of chitosan to modified nano-silicon dioxide is 5-7:10, and the stirring reaction time is 20-40min.
6. The drinking water tank coating according to claim 1, characterized in that: In step S4, the mass ratio of chitosan-coated nano-silica to the composite silane coupling agent is 10:2-3, the temperature of the heating and stirring reaction is 35-45° C., the time is 1-3 hours, and the composite silane coupling agent includes KH550 and KH560 in a mass ratio of 2-4:
5.
7. A method for preparing a drinking water tank coating according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Evenly mix epoxy resin, aqueous dispersant, aqueous defoamer, titanium dioxide, talcum powder, aqueous wetting agent and water, disperse at high speed, and grind to obtain component A; (2) Mixing the modified curing agent uniformly to obtain component B; When in use, component A and component B are evenly mixed in a mass ratio of 100:10-15, applied on the surface of the substrate, and cured at room temperature to obtain a coating.
8. The preparation method according to claim 7, characterized in that: The high-speed dispersion has a rotation speed of 1000-1200 r / min and a time of 20-30 min, and the grinding is performed to a fineness of <100 μm.
9. Use of the drinking water tank coating according to any one of claims 1 to 6 in the inner walls of drinking water tanks and drinking water transmission and distribution pipelines and equipment.
